2021
DOI: 10.1186/s12905-021-01570-4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of PLISSIT based counseling model on sexual function, quality of life, and sexual distress in women surviving breast cancer: a single-group pretest–posttest trial

Abstract: Background Diagnosis and treatment of breast cancer potentially leads to sexual dysfunction and sexual distress in women and negatively affects their quality of life (QoL). This study aimed at determining the effect of PLISSIT based counseling on sexual function, sexual distress, and QoL in women surviving breast cancer. Methods In this pre-test, post-test, single-group semi-experimental study, 65 women surviving breast cancer who were referred to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
0
14
0
2
Order By: Relevance
“…Various tools were described in the 35 included studies, (see Table 1 ). The most commonly used tool was the specific, stepwise model PLISSIT [ 39 , 48 – 50 , 54 , 61 , 66 , 75 ]. Two studies used the Extended PLISSIT model (EX-PLISSIT), which differs from the original PLISSIT model in that it is feedback-oriented while PLISSIT is a linear model [ 59 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Various tools were described in the 35 included studies, (see Table 1 ). The most commonly used tool was the specific, stepwise model PLISSIT [ 39 , 48 – 50 , 54 , 61 , 66 , 75 ]. Two studies used the Extended PLISSIT model (EX-PLISSIT), which differs from the original PLISSIT model in that it is feedback-oriented while PLISSIT is a linear model [ 59 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…A statistically significant improvement was found over time in the patient’s sexual functioning in 11 studies, mostly in studies among individual patients. Of these, five studies based their intervention on PLISSIT [ 38 , 48 , 50 , 54 , 59 ]. One study among couples indicated improvement in female sexual functioning and little improvement in male sexual functioning, without providing information about significance [ 62 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…P = 0.91, I 2 = 0%), there was no heterogeneity among the above studies. [24][25] Group problem solving therapy, a multimedia intervention showed the same positive signi cance on post-treatment sexual life satisfaction in breast cancer patients with the SMD of 0.44 (95% [CI] = 0.1-0.79). The change in prognosis Z = 2.5, p = 0.01.…”
Section: Age At Baseline Yearmentioning
confidence: 99%